State governance of Ukraine's international cooperation processes in the field of information relations - Shtyrov, Oleksandr; Verba, Svitlana (Public Administration and Regional Development, 2020)
The article deals with the peculiarities of the state management of the processes of international cooperation of Ukraine in the sphere of information relations, in particular the characteristics of the processes of international cooperation in the sphere of information relations, the analysis of state policy in the sphere of international relations to the ways of improving the mechanism of state governance of the sphere of information relations. International cooperation in the field of information relations takes place in the process of international information activity between two or more countries in the world market of services. The basis is to provide citizens, public authorities, businesses, institutions and organizations with official information (in documentary form or publicly announced) about various events and phenomena at the international level. This could be, for example, Ukraine's foreign policy activities, events in other countries, as well as in the purposeful distribution of information and information about our country outside Ukraine. International information relations are a rather new concept in the world, but in a very short time have become important and influential on the general economic, political and social situation of the participating countries. International outreach is to provide all participants (for example, citizens, government agencies, businesses) with information on Ukraine's foreign policy activities that are officially documented or publicly disclosed, and to purposefully disseminate comprehensive information outside the country. About Ukraine through, for example, the media, government agencies and citizens. It is established that in the current state of development of social development, as well as taking into account the situation of the Ukrainian and international information space, it is necessary to strengthen the role of the state in ensuring access of citizens of Ukraine to operational information and to guarantee the protection and reliability of the national information space.